2018
DOI: 10.1155/2018/9821738
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the Perforating Peroneal Artery following Ankle Arthroscopy

Abstract: The use of standard anterolateral and anteromedial portals in ankle arthroscopy results in reduced risk of vascular complications. Anatomical variations of the arterial network of the foot and ankle might render the vessels more susceptible to injury during procedures involving the anterior ankle joint. The literature, to our knowledge, reports only one case of a pseudoaneurysm involving the peroneal artery after ankle arthroscopy. Here, we report the unusual case of a 48-year-old man in general good health wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Therefore, the anterior perforating branch of the peroneal artery can be damaged by screw insertion from the anterolateral distal tibia. In fact, 2 cases of pseudoaneurysms involving the anterior perforating branch of the peroneal artery associated with the anterolateral portal during ankle arthroscopy have been reported 5,6 . When inserting a screw from the anterolateral distal tibia, surgeons should consider making the skin incision slightly larger and performing blunt dissection of the deeper soft tissues to avoid iatrogenic injury of the anterior perforating branch of the peroneal artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the anterior perforating branch of the peroneal artery can be damaged by screw insertion from the anterolateral distal tibia. In fact, 2 cases of pseudoaneurysms involving the anterior perforating branch of the peroneal artery associated with the anterolateral portal during ankle arthroscopy have been reported 5,6 . When inserting a screw from the anterolateral distal tibia, surgeons should consider making the skin incision slightly larger and performing blunt dissection of the deeper soft tissues to avoid iatrogenic injury of the anterior perforating branch of the peroneal artery.…”
Section: Discussionmentioning
confidence: 99%
“…A review about pseudoaneurysms around the foot and ankle revealed 5 cases of pseudoaneurysms of the peroneal artery, all of which were caused by ankle sprain 3 . Other reported causes of pseudoaneurysm of the peroneal artery around the foot and ankle include iatrogenic injuries, such as ankle arthroscopy 5,6 and internal fixation of an ankle fracture 7-9 . To the best of our knowledge, this is the first report describing a pseudoaneurysm of the peroneal artery after ankle arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic pseudoaneurysm formation is a rare complication following arthroscopy, with an incidence of 0.008%, although its diagnosis can go undetected ( 13 , 14 ). The most common pseudoaneurysm is that of the distal anterior tibial artery (d-ATA), and many clinical cases of such lesions have been published ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ). Other arteries can also be affected by pseudoaneurysm formation.…”
Section: Complications Of Ankle Arthroscopymentioning
confidence: 99%
“…As early as 1996, Ferkel et al indicated AA for patients with ankle pain, swelling, locking, and instability who did not respond to non-surgical treatment ( 5 ). Subsequently, the indications for AA have been expanded ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ). Table 1 summarises the current indications for AA.…”
Section: Introductionmentioning
confidence: 99%
“…1), Pseudoaneurysmen (▶ Abb. 2), arteriovenöse Fisteln, Dissektionen oder thrombotische Okklusionen verursachen [1,8,9].…”
Section: Penetrierende Gefäßverletzungenunclassified